Evaluation of Hemolysis Activity of Zerumbone on RBCs and Brine Shrimp Toxicity (Baghdad Science Journal, 2021)
Zerumbone is a well-known compound having anti-cancer, anti-ulcer, anti-inflammatory and anti-hyperglycemic effects. During its use for the disease treatment, the membrane of erythrocyte can be affected by consumption of this bioactive compound. The current study was the first report of investigation of the hemolytic activities on human erythrocytes and cytotoxic profile of zerumbone. The toxicity of zerumbone on human erythrocytes was determined by in vitro hemolytic assay. Brine shrimp lethality assay was used to evaluate the cytotoxic effect of zerumbone at concentrations 10, 100 and 1000 μg/mL. The human erythrocyte test showed no significant toxicity at low concentrations, whereas hemolytic effect was amplified up to 17.5 % at the highest concentration. The half lethal concentration (LC50) value of zerumbone against brine shrimp was less than 1000 µg /mL (LC50=190 µg/ml) showing the significant toxic nature of this compound. These results provide a baseline in terms of the toxicity of therapeutic formulations from this compound to membrane erythrocytes with a great attention to the highest concentrations, which paves promise for drug development.